TUNGKU BAKAR BRIKET UNTUK SKALA INDUSTRI MENENGAH KEBAWAH DENGAN PENAMBAHAN PENAMPUNGAN HASIL PEMBAKARAN (Jurnal Inovasi Mesin, 2022)
Stove design is basically made to achieve high combustion efficiency. The briquette stove performance test is also determined by several factors including time, temperature and combustion air quality. The type of briquette stove depends on the user sector, the type of stove that is currently on the market has an efficiency of between 31-33%. The briquette stove is not yet fully in demand by the public, this is because the briquette stove still has deficiencies, especially in the flame extinguishing operating system. Then a briquette stove was designed for households equipped with a fuel use control system so that what was left could be used for the next need.